Characterization of a Surface Glycoprotein from Echinococcus multilocularis and Its Mucosal Vaccine Potential in Dogs - Kouguchi, Hirokazu; Matsumoto, Jun; Nakao, Ryo; Yamano, Kimiaki; Oku, Yuzaburo; Yagi, Kinpei (PloS one, 2013)
Alveolar echinococcosis is a refractory disease caused by the metacestode stage of Echinococcus multilocularis. The life cycle of this parasite is maintained primarily between foxes and many species of rodents; thus, dogs are thought to be a minor definitive host except in some endemic areas. However, dogs are highly susceptible to E. multilocularis infection. Because of the close contact between dogs and humans, infection of dogs with this parasite can be an important risk to human health. Therefore, new measures and tools to control and prevent parasite transmission required. Using 2-dimensional electrophoresis followed by western blot (2D-WB) analysis, a large glycoprotein component of protoscoleces was identified based on reactivity to intestinal IgA in dogs experimentally infected with E. multilocularis. This component, designated SRf1, was purified by gel filtration using a Superose 6 column. Glycosylation analysis and immunostaining revealed that SRf1 could be distinguished from Em2, a major mucin-type antigen of E. multilocularis. Dogs (n=6) were immunized intranasally with 500 µg of SRf1 with cholera toxin subunit B by using a spray syringe, and a booster was given orally using an enteric capsule containing 15 mg of the same antigen. As a result, dogs immunized with this antigen showed an 87.6% reduction in worm numbers compared to control dogs (n=5) who received only PBS administration. A weak serum antibody response was observed in SRf1-immunized dogs, but there was no correlation between antibody response and worm number. We demonstrated for the first time that mucosal immunization using SRf1, a glycoprotein component newly isolated from E. multilocularis protoscoleces, induced a protection response to E. multilocularis infection in dogs. Thus, our data indicated that mucosal immunization using surface antigens will be an important tool to facilitate the development of practical vaccines for definitive hosts.